Response duration tracks confidence - Hanbei Zhou; Rui Zhe Goh; Ian Phillips; Chaz Firestone (Proceedings of the National Academy of Sciences, 2026)
The timing of behavioral responses is among the most robust signatures of cognitive processing—with easier, more accurate, and more confident judgments typically made more quickly. But which aspects of response timing carry these signals? Whereas the time taken to initiate a response (e.g., the interval between stimulus onset and keypress) is one of the most popular and informative measures in experimental psychology, another aspect of response timing is its duration (e.g., how long the key is held down before being released). Here, across three preregistered experiments spanning perceptual and higher-cognitive tasks, we demonstrate that response duration reliably predicts subjective confidence, over and above response initiation time. When detecting faces (Experiment 1), judging motion coherence (Experiment 2), and answering trivia questions (Experiment 3), subjects held down a response key longer during trials in which they subsequently reported lower confidence in their judgments, as if making these judgments in a tentative fashion. In all cases, response duration accounted for variance in confidence that was not predicted by response initiation time. Our results suggest that response duration itself carries independent information about cognitive processing, advancing a useful and ubiquitously available tool to complement traditional response time measures in the study of cognition.